PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PELANGGAN OJEK ONLINE GOJEK - Gunawan, Wely Hadi; Watulandi, Micki (Universitas Kuningan, 2024)
This study aims to analyze the impact of price, promotion, and service quality on customer satisfaction among Gojek users. The research adopts descriptive and verification methods and employs purposive sampling to select 100 respondents who are Gojek users in Cirebon City. Data collection involves distributing questionnaires and utilizing Likert scale measurements. The collected data are analyzed using SPSS 25 software. The findings reveal that: (1) price has a significant positive effect on customer satisfaction, (2) promotion does not significantly influence customer satisfaction, (3) service quality positively and significantly impacts customer satisfaction, and (4) collectively, price, promotion, and service quality significantly influence customer satisfaction.